IMPROVING STUDENTS’ SPEAKING PERFORMANCE THROUGH STORYTELLING - RINNA NURLINNA (Journal of English Education Program (JEEP), 2018)
This paper investigates the effectiveness of the use of storytelling to improve students’ speaking performance in English teaching learning process. Particularly, the use of storytelling was expected to give a positive effect to improve students’ speaking ability. The problem in this research is whether storytelling is effective to improve students’ speaking performance and what is the students’ perception in speaking by using storytelling. The population of this study was all the eighth grade students of SMPN 1 Sadananya in the academic year 2013/2014 consisting of 193 students. The writer took 50 students as sample of the research that consisted of class 8th A with 25 students as experimental group and class 8th C with 25 students as control group as sample of the research. The instruments are speaking test and questionnaire. Speaking test used to collect data were pre-test and post-test to Experimental and Control groups. The speaking test is in the form of selecting one of topics and practices it to be performed by each student in front of the class. They served to measure students’ ability to speak specifically by using storytelling. Meanwhile, questionnaire is in the form of the question that was about the statements of students’ perception on the use of storytelling to improve their speaking performance. From the research that had been carried out, the result of the research from two research questions were from the first research question can be drawn a conclusion that storytelling is effective to improve students’ speaking performance. Therefore, the writer could conclude that the teaching speaking by using storytelling is beneficial to be implemented by English teachers in order to improve the students’ speaking performance. Based on the result of this study it is suggested that storytelling be applied to teach English speaking performance, especially junior high school students.